Neutralization-based seroprevalence of Toscana virus and sandfly fever Sicilian virus in dogs and cats from Portugal - Alwassouf, Sulaf; Maia, Carla; Ayhan, Nazli; Coimbra, Monica; Cristovao, Jose Manuel; Richet, Herve; Bichaud, Laurence; Campino, Lenea; Charrel, Remi N (Journal of general virology, 2016)
Sandfly-borne phleboviruses are endemic in the Mediterranean basin. However, levels of exposure of human and animal populations are inadequately researched. Toscana virus (TOSV) is present in Portugal where it causes human infection and disease; in contrast there are few data for sandfly fever Sicilian virus (SFSV) which has neither been isolated nor detected by molecular tests and for which there are only limited serological data. The sera collected from 1160 dogs and 189 cats in southern Portugal were tested for the presence of neutralizing antibodies against TOSV and SFSV, two viruses recognized as distinct serocomplexes in the Mediterranean region. Our data showed (i) seropositivity to TOSV and SFSV in dogs at a rate of 6.8 and 50.8 %, respectively, and (ii) that 3.7 % of cats were seropositive for TOSV. TOSV findings are in line with previous results obtained with less stringent serological assays. Our results for SFSV in dogs clearly indicate that the virus is circulating widely and that humans may be exposed to infection via the dogs. Although the presence of SFSV was suggested by haemagglutination inhibition in 4/1690 human sera in 1974, this is the first time, as far as we know, that SFSV has been shown to circulate so widely in dogs in Portugal. Future studies should be directed at isolating strains of SFSV in Portugal from dogs, humans and sandflies collected in high prevalence regions. As dogs appear to be good sentinels for SFSV, their role as a possible reservoir in the natural cycle should also be considered.
Keywords: séroepidemiologické studie; psi; zvířata; Phlebotomus Fever; Antibodies, Neutralizing; horečka pappataci; protilátky virové; virus horečky pappataci; Antibodies, Viral; Animals; Cats; Cat Diseases; Dogs; nemoci koček; neutralizující protilátky; Portugalsko; Sandfly fever Naples virus; Female; Male; ženské pohlaví; Portugal; mužské pohlaví; nemoci psů; kočky; Dog Diseases; Seroepidemiologic Studies; Phlebovirus